When a city embraces its paradox : the exploration of incremental waste mining of a decommissioned landfill site and its gradual transformation into a productive public space - Lethugile, Goabamang (School of Architecture, Planning and Geomatics, 2016)
Today, with the majority of the world's population now living in urban areas. the possibility and urgent need to provide them with adequate public spaces has never been greater for the planet. Where public places and space itself are lacking. many cities across the world are today investing in projects of reclaiming valuable land to create livable public spaces that respond to and improve social, economic, and environmental values. Such projects include reclaiming of derelict sites which are characterized mainly by poor environmental and physical conditions. The redevelopment of these types of sites has received a lot of attention in the past few years. Their transformation into public spaces represents a significant enhancement to the quality of life and land use. and at the same time. marks new commitment to the transformation of once· condemned sites. to new cultural and environmental uses. Landscape architects such as Peter Latz. James Comer and Bruce Mau have shown how to create culturally stimulating landscapes with a Iarge variety of uses and activities arising out of the derelict remains of past industry. (Loures and Panagopoulos. 2006) Derelict or lost spaces such as the ones created by closed landfills and closed down industrial sites provide possibilities of generating productive public spaces that could serve to address the needs of the growing population. Contemporary approaches to these sites are mostly driven by the idea of reclaiming space for a variety of uses, from the reuse of an industrial area. to conversion Into housing or a park. It is the assumption that these types of sites, because of their high degree of complexity and contestation. are particularly suited to test and develop different theoretical and practical approaches to the redesign of public or mixed-use open spaces. (Langhorst. 2009) .